Association between economic strain, family strength and depression among low-income drug addict wives in Malaysia - Arshat, Zarinah; Ahmad Shahril, Nurul Saidatus Shaja’ah; Adnan, Haikal Anuar (Human Resources Management Academic Research Society (HRMARS), 2024)
This study aims to investigate the association between economic strain, family strength and depression. A total of 132 low-income drug addict wives were selected in this study using purposive sampling. Participants completed a set of questionnaire packages that included the Malaysian Family Strengths Scale (MFSS), Economic Strain Scale (ESS), and Zung’s Self-Rating Depression Scale (SDS). The results of path analysis revealed a direct association between family strength and depression as well as economic strain and depression. However, results showed that economic strain was not associated with family strength. Further analysis of the mediation effect was conducted utilising bootstrapping techniques. The findings revealed that the influence of economic strain on depression through family strength was insignificant. This study implies that when low-income drug addicts’ wives perceive that they have a high level of family strength, they tend to have low depression. While, if they experience a severe economic strain, they tend to have high depression. The present study suggests a replicated investigation using probability sampling method to achieve a wider generalization of the research findings. It is also recommended for future researchers to conduct a longitudinal study particularly examining the long-term impact of economic strain and family strength on later depression experienced by this population.